Marketing and Value Chain Analysis of Mandarin at Jorayal Rural Municipality of Doti, Nepal - Kathayat, Pawan; Bhatta, Kiran Prasad (Contemporary Research: An Interdisciplinary Academic Journal, 2023)
The yearly decline in mandarin production, one of the important citrus fruit in the mid-hills of Nepal could be attributed to underdeveloped and non-systematic market and lack of value-chain participation by farmers leading to low profitability and hence reducing their motivation. So, this research explores market and value chain of mandarin sub-sector through survey of 100 households from Jorayal rural municipality of Doti district using semi-structured questionnaires. Results showed that the average production of selected mandarin farmers is 1.8 Mt with income of Rs. 24,059 but considering family labor gross margins are negative. The dominant marketing channel is FarmersàCollectors, with around 92% of sales volume. Among the different types of collectors, local ones are dominant market players although price offered is higher for those coming from outside the district (Rs.58/kg) compared to local collectors (Rs. 50/kg), with producer's share being 40% and 35%, respectively. Monopoly of local collectors is high but for local relationship farmers are compelled to sell to them. Due to remoteness of the area, there are low/no value chain actors and hence marketing efficiency is also low. The major problem in marketing is found to be the low market price along with the unavailability of storage facilities or collection centers. Low networking of farmers is also contributing to reduction of the marketing efficiency and hence they are found not to be interested to scale-up their mandarin farms. Cooperative marketing may be one of the best options to increase the bargaining power of small-scale and scattered farmers.